Optimalisasi Human Resource Management Dengan Metode AHP Untuk Pemberian Bonus Karyawan PT. Talang Gugun Sari Nusantara - Yuliandri, Mario; Muhammad, Abulwafa; Lusinia, Shary Armonitha (Riset Sinergi Indonesia (RISINDO), 2025)
PT Talang Gugun Sari Nusantara already has dozens of employees in each branch, each employee has various criteria in every job. Therefore, PT Talang Gugun Sari Nusantara has a way to improve the performance of every employee. By giving bonuses to employees who do their work well and in accordance with the Company's wishes. PT Talang Gugun Sari Nusantara previously conducted an assessment in a manual way that made its assessment irrelevant to the circumstances that occurred. With this problem, the company needs a Decision Selection System using the Analysis Hierarchy Process method to assess employees with several criteria such as attendance, sales of each employee, responsibility, and manners. The research conducted aims to build a software on